2019
DOI: 10.1126/science.aau6520
|View full text |Cite
|
Sign up to set email alerts
|

Germline selection shapes human mitochondrial DNA diversity

Abstract: Approximately 2.4% of the human mitochondrial DNA (mtDNA) genome exhibits common homoplasmic genetic variation. We analyzed 12,975 whole-genome sequences to show that 45.1% of individuals from 1526 mother–offspring pairs harbor a mixed population of mtDNA (heteroplasmy), but the propensity for maternal transmission differs across the mitochondrial genome. Over one generation, we observed selection both for and against variants in specific genomic regions; known variants were more likely to be transmitted than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
217
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(243 citation statements)
references
References 59 publications
19
217
0
Order By: Relevance
“…2) 7,20,21 . As previously reported 22,23 , mutational spectrum indicated a high transition to transversion (Ti/Tv) ratio of 16.44 ( Supplementary Fig. 3).…”
Section: Resultssupporting
confidence: 82%
“…2) 7,20,21 . As previously reported 22,23 , mutational spectrum indicated a high transition to transversion (Ti/Tv) ratio of 16.44 ( Supplementary Fig. 3).…”
Section: Resultssupporting
confidence: 82%
“…However a detailed analysis of the exceptions (for example, Figure S1 insertions panel) revealed that nearly all of them mapped between positions 300 and 316, a region with homopolymer tracts known to be associated with misalignment errors 4,17 . Other homopolymer tracts are at mt positions: 66-71, 300-316, 513-525, 3106-3107, 12418-12425 and 16182-16194 4 . Calls in these regions may be inaccurate in both HelixMTdb and MITOMAP, and should be considered with caution.…”
Section: Mitochondrial Dna Variation In 196554 Individualsmentioning
confidence: 99%
“…Mitochondrial DNA can be uniform in sequence (homoplasmic) or can have variable sequences (heteroplasmy) within an individual cell. In addition, their unequal inheritance during cell division may result in changes to mutational load (% of the mitochondria carrying the mutation) during both the lifespan of an individual and across different cell types or tissues 4 . For individuals with heteroplasmic deleterious variants, those differences in mutational load can lead to varying phenotypic presentations of the same disease 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The race for gene discovery is actively ongoing and does not seem to end any soon. Within this scenario, the mtDNA still represents a diagnostic challenge due to the complexities of this genome, its variability and the different pathogenic potential that variants and genetic backgrounds may express in human populations [142,143].…”
Section: Current Challengesmentioning
confidence: 99%